Woman's eye, woman's hand : making art and architecture in modern India : a collection of essays - Ruggles, D. Fairchild
Post-independence, a generation of Indian women entered career fields such as architecture and design that had previously been closed to them. These educated professionals emerged as a pronounced political force - becoming important patrons of art, architecture, and public space - and increasingly became seen as the arbiters of taste and key shapers of the built environment. The essays in this volume address these developments and ask if these women produce art and architecture that specifically reflect a feminine perspective. They also explore how these women, otherwise invisible and largely excluded from public spaces, gained a voice in these male-dominated fields. A pathbreaking reassessment of the contribution of women artists and architects to the modern Indian landscape, Woman's Eye, Woman's Hand looks at these questions through both the frame of gender as well as through the frame of family lineage, with particular attention to the continuing importance of women's patronage of the arts.